2020
DOI: 10.32322/jhsm.643639
|View full text |Cite
|
Sign up to set email alerts
|

Yoğun bakım ünitesinde ortalama platelet hacmi ve platelet dağılım hacminin mortaliteye etkisi

Abstract: Background and Aim: This study aimed to determine the mean platelet volume (MPV) and platelet distribution width (PDW) values of intensive care patients, and show the relationship between these parameters and mortality. Material and Method: In the present study, 284 patients who were hospitalized in the intensive care unit were retrospectively analyzed. MPV and PDW values of the patients when they first hospitalized, their last MPV and PDW values before they died or were discharged, their ages and duration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In another study with 82 survivors and 25 non-survivors, both the admission MPV and last MPV values were higher on non-survivor group than survivors [22] . In the study performed by Gencay et al, [23] while the first and last MPV values were different in the deceased group, there was no significant difference between the first and last MPV values of the discharged patients were found. In our study, in accordance with the above-mentioned studies, it was observed that besides the first and last MPV values, the difference and ratio between them were also associated with mortality.…”
Section: Discussionmentioning
confidence: 76%
“…In another study with 82 survivors and 25 non-survivors, both the admission MPV and last MPV values were higher on non-survivor group than survivors [22] . In the study performed by Gencay et al, [23] while the first and last MPV values were different in the deceased group, there was no significant difference between the first and last MPV values of the discharged patients were found. In our study, in accordance with the above-mentioned studies, it was observed that besides the first and last MPV values, the difference and ratio between them were also associated with mortality.…”
Section: Discussionmentioning
confidence: 76%
“…Inflammatory cytokines are known to induce the release of large platelets from the bone marrow by stimulating thrombopoiesis 10 . It has been established that MPV is a key factor associated with mortality in many diseases 11,12 . However, the prevalence of thrombocytopenia has been emphasized in many studies 13 .…”
Section: Introductionmentioning
confidence: 99%
“…In Zhong et al's research with 85 cases, high MPR levels were spotted to be an independent risk factor for severe pneumonia in COVID-19 cases (18). Guclu et al found that the decreased MPV values were associated with mortality in the follow-up of the COVID-19 cases (49), in contrast to the other studies supporting a significant relationship between high MPV and mortality in patients hospitalized in the ICU (50). In a mortality study with 100 patients, it was found that MPR is not significantly associated with mortality (29).…”
Section: Discussionmentioning
confidence: 94%